An Effective, Entertaining and Interesting Tool to Identify Students' Misconceptions: The Concept Cartoons - Önal, Halil (Southeast Asia Early Childhood Journal, 2023)
The aim of this research is to determine the students' misconceptions of using concept cartoons and to evaluate the lessons taught with concept cartoons according to the students' opinions. The model of the research is the case study, which is one of the qualitative research methods. Participants are a total of 82 students, attending the 3rd grade (8 years old). Descriptive analysis method was used in the analysis of the data. Considering the results of the research, although most of the students chose the right character and stated the reasons for finding operational mistakes, it was determined the students who stated that they agreed with the characters in the wrong instruction and put forward reasons, most of which included misconceptions. For the lessons taught with concept cartoons, students; that they like concept cartoons very much, that they create curiosity and excitement in themselves, by using concept cartoons, they will not make mistakes, and even if they make mistakes, they will be able to realize and correct their mistakes by discussing with their friends and teachers, that the lessons cannot always be done with concept cartoons, that the teachers will make this decision stated as. As a result, it has been concluded that the use of concept cartoons is effective in identifying students' misconceptions and understanding their thinking processes, and that concept cartoons can be used easily in classrooms, increasing the interest and motivation of students, and enabling them to learn while having fun.